The Gains from Variety in the European Union - Lukas Mohler; Michael Seitz (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2010)
Over the last decade, European Union members have experienced a dramatic increase in imports. This increase was accompanied by a strong growth in the number of imported goods and trading partners, indicating positive welfare gains for consumers via an extended set of consumption possibilities, as pointed out in the "New Trade Theory". In this paper, we apply the methodology developed by Feenstra (1994) and Broda and Weinstein (2006) to estimate structurally the gains from imported variety for the 27 countries of the European Union using highly disaggregated trade data at the HTS-8 level from Eurostat for the period of 1999 to 2008. Our results show that, within the European Union, especially “newer” and smaller member states exhibit high gains from newly imported varieties. Furthermore, we find that the vast majority of the gains from variety for consumers stem from intra-European Union trade.
urn:nbn:de:bvb:19-epub-11477-8
Keywords: F12; F14; 330; European Union; Welfare Gains from Trade; Trade in Variety; Internationale Wirtschaft; EU-Binnenhandel; Außenhandelsgewinn; Import; Diversifikation; Schätzung; EU-Staaten; EU-Mitgliedschaft